2021
DOI: 10.1016/j.bioactmat.2021.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Advances in coatings on magnesium alloys for cardiovascular stents – A review

Abstract: Magnesium (Mg) and its alloys, as potential biodegradable materials, have drawn wide attention in the cardiovascular stent field because of their appropriate mechanical properties and biocompatibility. Nevertheless, the occurrence of thrombosis, inflammation, and restenosis of implanted Mg alloy stents caused by their poor corrosion resistance and insufficient endothelialization restrains their anticipated clinical applications. Numerous surface treatment tactics have mainly striven to modify the Mg alloy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 244 publications
(341 reference statements)
1
62
0
1
Order By: Relevance
“…However, bare magnesium alloy stents are notorious for rapid corrosion or biodegradation, leading to devastating effects described in Section 4.3. Hence, as magnesium-based biodegradable coronary stent implantation is highly regarded as a potential therapeutic application to coronary heart disease, one of the leading causes of death globally [79][80][81], extensive ongoing investigations centered around strategies to control its degradation rate [82,83]. The strategies proposed are consistent with our earlier discussion in Section 4.3.…”
Section: Cardiovascular Applicationssupporting
confidence: 64%
See 1 more Smart Citation
“…However, bare magnesium alloy stents are notorious for rapid corrosion or biodegradation, leading to devastating effects described in Section 4.3. Hence, as magnesium-based biodegradable coronary stent implantation is highly regarded as a potential therapeutic application to coronary heart disease, one of the leading causes of death globally [79][80][81], extensive ongoing investigations centered around strategies to control its degradation rate [82,83]. The strategies proposed are consistent with our earlier discussion in Section 4.3.…”
Section: Cardiovascular Applicationssupporting
confidence: 64%
“…It includes improving the design of the alloy and modifying the surface with coating technologies. Thus far, the literature has suggested that incorporation of both strategies would work [82], although early in vivo trials have demonstrated mixed clinical outcomes [81]. Nonetheless, more research and advancements in this direction will likely persist in the coming years.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…Two principal implantable devices could be considered here, the vascular graft and the intravascular stent. However, this essay concentrates on the graft only; with stents, the situation is complicated by the use of drug elution methods, which have pharmacological activity [ 87 ] and by the use of biodegradable alloys, which operate by different mechanisms; these have been comprehensively reviewed in this journal very recently [ 88 ]. With respect to prosthetic vascular grafts, Zilla et al discussed the difficulties of encouraging graft endothelialization a number of years ago [ 89 ].…”
Section: Categories Of Bioactive Materialsmentioning
confidence: 99%
“…Creating surface coatings may help in overcoming this limitation. Moreover, functional coatings can further improve the biocompatibility of such alloys [113][114][115][116][117]. Several novels, multifunctional coatings are presented in Table 2, and some of these, along with others, are discussed in more detail below.…”
Section: New Challenges In Coatings On Biodegradable Mg Alloysmentioning
confidence: 99%